The Effect of Tax Incentives, Tax Socialization, and Law Enforcement on Motor Vehicle Tax Compliance in East Java - Loso Judijanto; Saida Said (Westscience Press, 2024)
This study examines the impact of tax incentives, tax socialization, and law enforcement on motor vehicle tax compliance in East Java, utilizing a quantitative approach. A sample of 140 respondents was surveyed using a Likert scale (1-5), and the data were analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that tax incentives (H1), tax socialization (H2), and law enforcement (H3) have positive and significant effects on motor vehicle tax compliance. Specifically, law enforcement emerged as the most influential factor, followed by tax incentives and tax socialization. These findings highlight the importance of well-structured tax policies, comprehensive taxpayer education, and robust enforcement mechanisms in enhancing tax compliance. The study offers valuable insights for policymakers seeking to improve tax collection efficiency and compliance rates among motor vehicle owners in East Java.